Family, Education and Inclusion of Deaf Children with Cochlear Implants: first results. - Ruiz Ariza, Deseada; Prados-Megías, Esther; Leite-Méndez, Analía Elizabeth; Cortés-González, Pablo (My University, 2023)
This contribution presents the progress of a doctoral research project that aims to respond to the needs and possibilities that families have to meet and provide educational support to a son or daughter who was born with profound deafness and who has undergone cochlear implantation. According to various researchers (Bruin, 2018; Holt, Beer, Kronenberger, Pisoni & Lalonde, 2012), cooperation between different educational agents is vital for the comprehensive development of minors, with the family being a first-order entity. There are few studies in this regard, hence the importance of recovering the experiences of families to develop an inclusive education.
Keywords: Sordos - Educación; Educación inclusiva; Inclusión; Implantes cocleares; Familia; Escuela